The expression of APE1 in triple-negative breast cancer and its effect on drug sensitivity of olaparib. Issue 10 (October 2017) - Chen, Tianran; Liu, Chuan; Lu, Heng; Yin, Mingzhen; Shao, Changjuan; Hu, Xiaoding; Wu, Jiaxue; Wang, Yajie
Triple-negative breast cancer is a kind of breast cancer with poor prognosis and special biological behavior, which lacked endocrine therapy and targeted therapy. We investigate the effect of human APE1 (apurinic/apyrimidyl endonuclease 1), a rate-limiting enzyme of base excision repair, on the prognosis in triple-negative breast cancer and drug sensitivity of olaparib. The expression of APE1 was detected by immunohistochemistry in the triple-negative breast cancer tissues and its effect on survival of triple-negative breast cancer patients was followed. To find whether APE1 effect the drug sensitivity in triple-negative breast cancer cells, the APE1-knockout HCC1937 cell line (triple-negative breast cancer cell line) was established by CRISPR/Cas9 system. Then, we use the wild-type and knockout one to test the drug sensitivity of olaparib. The expression of APE1 in triple-negative breast cancer tissues was significantly higher than that in the adjacent tissues (85.6% vs 14.4%) and its expression was related to tumor size (p < 0.05). We also found that it is an independent prognostic factor in patients with triple-negative breast cancer (overall survival, p = 0.01). In vitro assay, the half maximal inhibitory concentration of olaparib in HCC1937-APE1-KO was significantly increased (17.22 vs 91.85 μM) compared to the wild type. The growth curve showed that olaparib had a stronger lethality on HCC1937 compared to HCC1937- APE1-KO (p < 0.05 on day 3). HCC1937 resulted in more mitotic G2/M arrest and increased apoptosis rate after treatment with 40 μM of olaparib, while HCC1937-APE1-KO did not change significantly. When HCC1937 was treated with different concentrations of olaparib, it was found that APE1 expression decreased more significantly at 15 μM of olaparib was. In HCC1937-APE1-KO, the expression of endogenous poly (ADP-ribose) polymerase 1 was also less than that of HCC1937. These results suggested that the expression of APE1 was an important basis for the maintenance of poly (ADP-ribose) polymerase 1, and the deletion of APE1 may be related to the resistance of olaparib.